2004
DOI: 10.1089/scd.2004.13.382
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Proliferation and Expansion of Hematopoietic Progenitors Present in Mobilized Peripheral Blood from Normal Subjects and Cancer Patients

Abstract: In the present study, we have assessed, in a comparative manner, the in vitro proliferation and expansion potentials of hematopoietic progenitor cells (HPC) present in mobilized peripheral blood from normal subjects (MPB-n; n = 18) and cancer patients (MPB-c; n = 18). The latter included patients with breast cancer (BrCa; n = 8), Hodgkin disease (HD; n = 4), non-Hodgkin lymphoma (NHL; n = 3), and acute myeloid leukemia (AML; n = 3). Progenitor cells from normal bone marrow (BM) and umbilical cord blood (UCB) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In keeping with the concept mentioned earlier, we have observed that, when cultured in serumfree liquid cultures in the presence of a rich cytokine cocktail, progenitor cell-enriched Lin Ϫ cell populations derived from UCB show significantly higher in vitro growth capacities than equivalent populations from aMPB (9). The mechanisms responsible for this have not been elucidated.…”
Section: Introductionmentioning
confidence: 52%
“…In keeping with the concept mentioned earlier, we have observed that, when cultured in serumfree liquid cultures in the presence of a rich cytokine cocktail, progenitor cell-enriched Lin Ϫ cell populations derived from UCB show significantly higher in vitro growth capacities than equivalent populations from aMPB (9). The mechanisms responsible for this have not been elucidated.…”
Section: Introductionmentioning
confidence: 52%
“…Two (20 pathways of DC differentiation have been extensively studied in regard to their clinical applicability: differentiation of peripheral blood monocytes into DCs after exposure to various maturation stimuli 4,5 and differentiation of CD34 ϩ hematopoietic progenitors. 9,10,12 For therapy, autologous DCs are obtained to avoid major histocompatability complex restriction, but this is not good for the patient because the procedure requires much blood for therapy. In our study, allogeneic DCs were generated successfully from umbilical blood by culturing with GM-CSF, IL-4, and TNF-␣ and loaded with the lysate of allogeneic A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Altering DC differentiation, maturation with low expression of activating markers like CD1a, CD40, and CD83, and longevity may be mechanisms for immune suppression. 11,12,[16][17][18] Our data have shown that AgL-DCs are capable of inducing a strong antitumor response. In our study, immunohistofluorescent stain analysis showed that CD1a ϩ and CD83 ϩ mononuclear cells markedly infiltrate the established tumors of mice treated with AgL-DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The network input and output data were obtained from literature 1,2,[4][5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25]27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][46][47][48][49] for evaluation and prediction. Altogether 341 data were collected and summarized in Table 1.…”
Section: Network Input and Outputmentioning
confidence: 99%